Mindfulness and business education : developing self-aware future leaders - a practical guide - Rivers, Christine (Abingdon, Oxon ; New York, NY : Routledge, 2025)
Mindfulness and Business Education - Developing self-aware future leaders, is a practical guide for educators and academics with teaching responsibilities in business schools or colleges. Business schools have a responsibility to equip future leaders with the right knowledge and right skills to make right decision particularly in times of volatility, uncertainty, complexity, and ambiguity. This responsibility can only be met if business schools change the way they teach and develop self-aware future leaders grounded in the foundations of mindfulness. The book is divided into three parts: Why, What and How. Part one Why introduces the foundations of mindfulness, draws on history of business school development, and discusses leadership approaches presently taught in business schools. Part two What discusses ways of measuring mindfulness, the need for training business educators as mindfulness facilitators and its contextualisation in contemporary business topics such as wellbeing, sustainability, diversity, and artificial intelligence. Part three How provides cases studies and scripted resources for immediate use and implementation in extra-curricular or co-curricular activities, to design mindfulness-based modules and courses, to introduce mindfulness coaching as part of pastoral care and staff development and to develop mindfulness-driven business education strategies. This is an ideal book for those in business education looking to use mindfulness in the way they develop future managers and leaders-- Provided by publisher.
Keywords: Business education; Mindfulness (Psychology); BUSINESS & ECONOMICS / Careers / General